1989
DOI: 10.1128/mcb.9.3.914
|View full text |Cite
|
Sign up to set email alerts
|

Control of carbohydrate processing: increased beta-1,6 branching in N-linked carbohydrates of Lec9 CHO mutants appears to arise from a defect in oligosaccharide-dolichol biosynthesis.

Abstract: A correlation between increased 0-1,6 branching of N-linked carbohydrates and the ability of a cell to metastasize or to form a tumor has been observed in several experimental models. Lec9 Chinese hamster ovary (CHO) mutants exhibit a drastic reduction in tumorigenicity in nude mice, and this phenotype directly correlates with their ability to attach an increased proportion of "-1,6-branched carbohydrates to the G glycoprotein of vesicular stomatitis virus (J. Ripka, S. Shin, and P. Stanley, Mol. Cell. Biol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Lec8, Lec9, LEC10, LEC11, and LEC12. structural and enzymic studies, which identified the basis for the glycosylation change in each mutant (1,5,6,9,12,(26)(27)(28)(32)(33)(34)(35)(36)(37)(38); Krieger et al, in press). The N-linked carbohydrates in parental CHO cells would be expected to contain up to three or more lactosamine units (Gal 0-1,4-GlcNAc) (14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lec8, Lec9, LEC10, LEC11, and LEC12. structural and enzymic studies, which identified the basis for the glycosylation change in each mutant (1,5,6,9,12,(26)(27)(28)(32)(33)(34)(35)(36)(37)(38); Krieger et al, in press). The N-linked carbohydrates in parental CHO cells would be expected to contain up to three or more lactosamine units (Gal 0-1,4-GlcNAc) (14).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, amebic adherence was not apparently affected by the increased branching of N-linked carbohydrates that is characteristic of Lec9 and LEC10 mutants ( Table 1). Lec9 mutants synthesize an increased proportion of ,8-1,6-branched, N-linked carbohydrates (26,28), and LEC10 mutants add the bisecting GlcNAc to N-linked carbohydrates (1). It is of note that amebic adherence to Lec9 CHO cells was extremely sensitive to inhibition by Gal (98.8% inhibition).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For another perspective, we also examined skin fibroblasts metabolically labeled with [2- (37)(38)(39)(40). The enzymatic defects in these cell lines include reduced levels of polyprenol reductase activity (required for the biosynthesis of dolichol), and of mannosylphosphoryldolichol synthase (required for the biosynthesis of Man-P-Dol; see 37,39,45,46).…”
Section: Discussionmentioning
confidence: 99%
“…tein [Morrison and Lodish, 1975]. Normally in CHO cells, G protein is N-glycosylated at two sites [Stanley, 1982] and di-, mono-, and nonglycosylated forms can easily be separated by SDS-PAGE [Rosenwald et al, 1989].…”
Section: N-linked Glycosylation Of G Protein Of Vsv-infected Mi5-4 Cellsmentioning
confidence: 99%